BASED ON ABAQUS SINGLE POINT INCREMENTAL FORMING NUMERICAL ANALYSIS - ZHANG Yong; LI PengYang; WANG QuanDai; YAO ZiMeng; XU HaiFeng (Jixie qiangdu)
Single point incremental forming（ SPIF） is a new metal forming method without Die ＆cutting. Using this method,the product cycle shorten,the production costs reduced. The main process parameters of the single point incremental forming : tool diameter d、the incremental depth ΔZ、sheet thickness sthimpacting on the simulation results are analyzed using Abaqus. Law of sine on incremental forming reaction sheet thickness variation is verified through simulation,the law of sine draw sheet thickness greater than the numerical simulation of the distribution is analyzed. thickness distribution of the sheet metal forming is presented,it’s application is analyzed.